IMPLEMENTASI PERATURAN PRESIDEN NOMOR 116 TAHUN 2022 TENTANG SISTEM PENGAWASAN DAN PENGENDALIAN PELAKSANAAN NORMA, STANDAR, PROSEDUR DAN KRITERIA MANAJEMEN ASN - Yudi Bastianto; Simon Nisja Putra Zai (ITB AAS Indonesia Surakarta, 2023)
The President as the holder of government power is the highest authority in policy, professional development and ASN management. This means that the President is the highest state administrator in running the state government, especially in fostering ASN Management, so that the full power and responsibility rests with the President. So in this case a system of supervision and control of ASN Management is needed to support the implementation of the State Civil Service Agency (BKN) in assisting the president's duties as the highest ASN management supervisor, so that BKN as an institution that is given attributive authority based on Law Number 5 of 2014 concerning ASN to carry out their authority optimally in supervising and controlling the implementation of ASN management Norms, Standards, Procedures and Criteria (NSPK) nationally in order to realize good governance and clean governance. The results of this study indicate that the Implementation of Presidential Regulation Number 116 of 2022 concerning the supervision and control system for the implementation of ASN Norms, Standards, Procedures and Management Criteria has been carried out optimally by the State Civil Service Agency through the Wasdal Deputy, namely by accelerating acceleration after the Presidential Regulation concerning the Employee Monitoring and Control System. ASN Management Norms, Standards, Procedures and Criteria (NSPK) were promulgated on September 14, 2022.